Adaptation To Climate Change In Uganda: Evidence From Micro Level Data - Hisali, Eria; Birungi, Patrick; Buyinza, Faisal (Global environmental change, 2011)
This study employed data from the 2005/06 Uganda national household survey to identify adaptation strategies and factors governing their choice in Uganda's agricultural production. Factors that mediate or hinder adaptation across different shocks and strategies include age of the household head, access to credit and extension facilities and security of land tenure. There are also differences in choice of adaptation strategies by agro-climatic zone. The appropriate policy level responses should complement the autonomous adaptation strategies by facilitating technology adoption and availing information to farmers not only with regard to climate related forecasts but available weather and pest resistant varieties.
Keywords: Climate change;Adaptation;Multinomial logit